STRATEGI BERTAHAN HIDUP RUMAH TANGGA PETANI BUNGA POTONG PADA SAAT PANDEMI COVID-19 (Studi Kasus di Desa Pasirlangu, Kecamatan Cisarua, Kabupaten Bandung Barat, Jawa Barat) - Nurulhaqq Sariwibawa Ahmad Zaeni; Rani Andriani Budi Kusumo; Nur Syamsiah; Hepi Hapsari (Universitas Galuh, 2022)
The COVID-19 pandemic has had a negative impact both from an economic and non-economic perspective. Agriculture is one of the sectors affected by the COVID-19 pandemic, especially in horticultural commodities. Cut-flowers are horticultural commodities affected by the COVID-19 pandemic in addition to vegetables. Pasirlangu Village is one of the villages in Cisarua District that has been affected by the COVID-19 pandemic because the majority of the population works as farmers with cut flower farming. This study aims to describe the impact of the COVID-19 pandemic on cut flower farming in Pasirlangu Village and to find out the form of survival strategies carried out by cut flower farming households during the COVID-19 pandemic. The research method used is a qualitative method with a case study technique. The study reveals that the survival strategy carried out by cut-flower farming households during the COVID-19 pandemic to meet their household needs are by doing side jobs, increasing the work intensity, implementing a double income pattern, selling assets, reducing household expenses, borrowing money from financial institutions, and take advantage of the social network owned by the household.